The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.pjnns.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants in epilepsy

Abstract: People with epilepsy (PWE) frequently suffer from comorbid mood and anxiety disorders. Depression is one of the major psychiatric comorbidities having a negative impact on the quality of life in people with epilepsy. A review of the literature indicates that the majority of antidepressant-related seizures have been associated with either ultra-high doses or overdosing and, generally, the risk of antidepressant-associated seizures is low. Correspondingly, there is some evidence indicating that antidepressants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 44 publications
0
10
0
4
Order By: Relevance
“…SSRIs are a widely used type of antidepressant in the treatment of depression. Most studies have reported that SSRIs and antidepressants have antiepileptic effects on various experimental epilepsy models (24,25). For instance, in our published article, vortioxetine (5 and 10 mg/kg), a novel SSRI, suppressed epileptiform activity in the pentylenetetrazole (PTZ)-induced kindling model (15).…”
Section: Discussionmentioning
confidence: 85%
“…SSRIs are a widely used type of antidepressant in the treatment of depression. Most studies have reported that SSRIs and antidepressants have antiepileptic effects on various experimental epilepsy models (24,25). For instance, in our published article, vortioxetine (5 and 10 mg/kg), a novel SSRI, suppressed epileptiform activity in the pentylenetetrazole (PTZ)-induced kindling model (15).…”
Section: Discussionmentioning
confidence: 85%
“…However, tricyclic or tetracyclic antidepressants and norepinephrine-dopamine reuptake inhibitors should be avoided as the first choice due to their capacity to lower the seizure threshold. 33 A review of the literature indicates that maprotiline, high doses of clomipramine and amitriptyline (>200mg) and high doses of bupropion immediate-release formulation (>450mg) seem to be more frequently associated with seizures than other antidepressants. 34 Our study has several methodological limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Somado a isso, a perda da "resiliência" da rede neuronal poderia explicar o surgimento da crise. Os principais fatores epigenéticos relacionados às alterações de sinalização nas redes neuronais são a inflamação, estresse, drogas, e até mesmo os antidepressivos tricíclicos (AVANZINI et al, 2012;CHANG et al, 2018;GÓRSKA et al, 2018;MOSHÉ et al, 2014). A pesquisa acerca dos processos convulsivos e fármacos com novos mecanismos de ação, torna-se indispensável devido às controversas bases da fisiopatologia.…”
Section: Discussionunclassified